(untitled) (Observatorio Económico, 2009)
Have you ever wondered how much you contribute to climate change when you drink a glass of wine? For the vast majority of us, this question may seem irrelevant and even far-fetched. Today, however, the wine sector is preparing to have an answer. And it is doing so because the market demands it. Measurement of the “carbon footprint”—the trail of carbon emissions generated by the production and transportation of a product—is gaining strong ground in the main destinations of Chilean exports: Europe, the United States, and Japan. Continue reading...